Single-Port Laparoscopic Surgery Is Feasible and Safe for Hepatic Left Lateral Sectionectomy for Benign Liver Lesions - Yuan Cheng; Ze-sheng Jiang; Xiao-ping Xu; Wen-fa Huang; Guo-lin He; Chen-jie Zhou; Jia-sheng Qin; Yi Gao; Ming-xin Pan (Gastroenterology Research and Practice)
Background and Objectives. The feasibility and safety of single-port laparoscopic surgery for left lateral liver lobectomy are largely unknown. This study is aimed at comparing the effectiveness and safety between single-port laparoscopic (SPL) and conventional multiport laparoscopic (CL) surgeries for hepatic left lateral sectionectomy. Methods. A total of 65 patients receiving laparoscopic hepatic left lateral sectionectomy between January 2008 and July 2015 were included and divided into the SPL group (n=40) and the CL group (n=25). Results. There was no significant difference in the operative time, estimated intraoperative blood loss, length of hospital stay, and incidences of postoperative complications (biliary leakage, hemorrhage, and contusion at incision) between groups (all P>0.05). However, the SPL group had a significantly lower VAS pain score (at 24 h but not 7 days postoperation) and higher cosmetic satisfaction scores (at both 2 months and 6 months postoperation) than the CL group (all P<0.01). Moreover, multivariate linear regression analysis further confirmed the superior pain score and cosmetic outcome in the SPL group. Conclusions. Single-port laparoscopic hepatic left lateral sectionectomy is a safe and feasible treatment for patients with lesions in the left hepatic lobe. Patients with benign lesions in the left hepatic lobe are more suitable to receive single-port laparoscopic hepatic left lateral sectionectomy than those with malignancies.